Transformative Approaches to Universal Health Care: Towards Achieving Health Equity Framework in the Local Government Level - Dolores T. Quiambao; Milette Q. Sanchez (Future Science / FSH-PH Publications, 2026)
Universal Health Care (UHC) is one of the critical policies ensuring the equitable access to quality health services without experiencing financial hardship. In the Philippines, UHC was institutionalized through Republic Act No. 11223 and reinforced the role of the Local Government Units (LGUs) in implementing health reforms and modification responsive to the community needs. This study evaluated the transformative approaches to Universal Health Care (UHC) towards the development of a health equity framework in the local government level. It utilized the convergent mixed-method research design combining quantitative analysis of health outcome indicators across selected Local Government Units implementing UHC integration sites along with qualitative interviews with local health officers, policy implementers, and community stakeholders. The premise of the exemplified transformative approaches in the utilization and implementation to UHC in the local government ensure the provisions of comprehensive delivery of health services, health financing, governance and leadership. The major themes that emerged from the study were: (1) primary healthcare orientation, (2) equity-oriented health system, (3) multi-sectorial collaboration, (4) financial protection mechanisms and (5) continuous monitoring and evaluation. The manifested themes from this study supplemented the health equity framework in the local government level to strengthen the health system, institutionalize health regulation, ensure the stability of the health services, and provide equity-oriented healthcare system.